(untitled) (diségno, 2021)
An emblematic synthesis of the homonymous project developed in 1964 within the Archigram Group by Ron Herron (1930-1994) and Warren Chalk (1927-1987) with the collaboration of Frank Brian Harvey for the drafting of the graphics, the plate A Walking City is part of a series of drawings that prefigure the futuristic idea of a city organised in mobile mechanical units, imbued with a post-apocalyptic atmosphere and characterised by a programmatically utopian vocation. [read more]